Sulfur-functionalized graphene and its use as a Li-S battery cathode

Sulfur-functionalized graphene addresses conductivity and polysulfide shuttling issues in lithium-sulfur batteries by covalently bonding sulfur chains to graphene, achieving high specific capacity and stable cycling performance.

JP7613775B2Active Publication Date: 2025-01-15UNIV PALACKEHO V OLOMOUCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023520362
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-02
Filing Date
2021-05-04
Publication Date
2025-01-15
Estimated Expiration
2041-05-04

AI Technical Summary

Technical Problem

Lithium-sulfur batteries face challenges such as poor conductivity of sulfur, large volume changes during charging and discharging, low coulombic efficiency due to soluble lithium polysulfide shuttling, and fast capacity fade, limiting their practical development and efficiency.

Method used

A method to prepare sulfur-functionalized graphene by treating fluorinated graphite with metal polysulfides, resulting in covalently bonded sulfur chains on the graphene surface, enhancing conductivity and immobilizing polysulfides, thereby inhibiting the shuttle effect.

Benefits of technology

The method achieves high sulfur loading and stable cycling, providing high specific capacity and improved cycling stability, with sulfur-functionalized graphene demonstrating capacities up to 912mAhg⁻¹ and maintaining 96.8% coulombic efficiency after 100 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613775000004
    Figure 0007613775000004
  • Figure 0007613775000005
    Figure 0007613775000005
  • Figure 0007613775000006
    Figure 0007613775000006
Patent Text Reader

Abstract

The present invention provides a method for producing sulfur-functionalized graphene, comprising the steps of: a) providing a dispersion of fluorinated graphite; b) subjecting the dispersion of fluorinated graphite to ultrasonic treatment and / or mechanical treatment and / or thermal treatment; c) Preparation of metal polysulfides starting from metal sulfides and sulfur; d) The product from step b) is mixed with the product from step c) for 10-110 min. o contacting at a temperature in the range of C; e) Separating the solid product formed in step d) from the solution. Further provided is sulfur-functionalized graphene with high sulfur loading obtained by this method, and its use in an electric cell.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [Technical field] The present invention relates to a novel method for preparing sulfur-functionalized graphene, which produces graphene with high sulfur loading and low residual fluorine content. The resulting material makes it possible to form electrodes for lithium-sulfur batteries with high specific capacity and high cycling stability.

[0002] [Background technology] Lithium-ion batteries (LIBs) are rechargeable energy storage systems that have dominated the electronics market since the early 1990s as the power source for portable and larger devices. However, with the rapid increase in portable devices and electric vehicles used in personal, professional, and military applications, the demand for batteries with higher performance and lower cost is also increasing. Thus, considerable research efforts have been put into developing advanced electrical energy storage devices that can provide high energy density. The lithium-sulfur battery (LSB) has a high theoretical specific capacity (1672 mAhg -1 ) and specific energy (2600Whkg -1 ), which could provide a very promising energy storage system alternative. Moreover, sulfur is environmentally friendly, naturally abundant, and an important by-product of the petroleum industry, which makes it attractive for its variants and commercialization in high-tech fields such as portable energy storage. However, several bottlenecks, such as the poor conductivity of sulfur and its large volume change upon charging and discharging, hinder the practical development of LSBs and limit their efficient and long-life operation. More importantly, the soluble lithium polysulfides (Li2S) formed as by-products during the charge / discharge process n , n≧4) results in low coulombic efficiency, low sulfur utilization, and fast capacity fade.

[0003] Various strategies have emerged to address the above-mentioned issues, such as fabricating cathodes using materials that act as sulfur hosts to make sulfur more stable, or using functional separators to prevent the shuttle of lithium polysulfides. The design of composite cathodes to achieve high sulfur loading, utilization, and stability is the first key step to exploit the features of LSB. In this regard, nanostructured carbon-based materials are usually used, as they exhibit high porosity to accommodate sulfur, good electrical conductivity, large surface area, and excellent mechanical properties. In a pioneering study (XLJi et al. Nat.Mater. 2009, 8, 500-506), ordered mesoporous carbon for sulfur encapsulation was utilized to improve sulfur utilization and suppress the "shuttle effect". However, such conventional porous carbon hosts lead to poor cycling stability due to the weak interaction between polar polysulfides and non-polar carbons, highlighting the need for different carbon chemistries and composites, such as designer carbons with tailor-made chemical groups on their surfaces. Such functional groups should effectively immobilize polysulfides and limit the "shuttle effect" during the charge / discharge process for stable cycling. In addition, when replacing porous carbon for physical entrapment of sulfur, appropriately functionalized graphene can be used as a building block for the controlled assembly of highly stabilized / highly sulfur-loaded cathodes, which further provide better electrical conductivity. Another approach to block the "shuttle effect" is to replace elemental sulfur by short-chain polysulfides covalently bonded to the surface of carbon, preferably on graphene for higher electrical conductivity, which alleviates the insulating nature of sulfur to some extent.

[0004] To achieve this, we considered fluorinated graphite and its few-layered fluorographene analogue (hereafter simply called fluorographene), which is the starting material for the preparation of several covalently functionalized few-layered graphene derivatives (hereafter simply called graphene derivatives) since the carbon atom is electrophilic (actually the electrophilicity of the carbon radical defect) and therefore highly reactive with many nucleophiles even under mild conditions. Previous work (V.Urbanova et al. Adv. Mater, 2015, 27, 2305-2310) showed the first example of covalent functionalization of fluorographene with thiol / sulfhydryl groups (-SH) by simple nucleophilic substitution of fluorine atoms in polar solvents. Nevertheless, the sulfur in the -SH group is already in a reduced state and therefore not suitable for battery cathode materials. Another problem in graphene-SH derivatives was that the carbon atom is bonded to only one S atom, resulting in a very small S content (5 atomic % as reported). DISCLOSURE OF THEINVENTION

[0005] The present invention provides a method for preparing sulfur-functionalized graphene, comprising the steps of: a) providing a dispersion of fluorinated graphite; b) subjecting said dispersion of fluorinated graphite to ultrasonic treatment and / or mechanical treatment and / or heat treatment; c) preparing a metal polysulfide starting from a metal sulfide and sulfur; d) The product from step b) is mixed with the product from step c) at 10 to 110°C. o contacting at a temperature in the range of C; e) Separating the solid product formed in step d) from the solution.

[0006] The term "fluorinated graphite" includes fluorographite, graphite fluoride, graphite fluoride, and exfoliated forms of these materials. Fluorinated graphite is also sold under the names poly(carbon monofluoride), carbon monofluoride, or poly(carbon fluoride). The initial content of fluorine in the starting fluorinated graphite is typically at least 40 atomic %, more preferably at least 45 or at least 50 atomic %, relative to the total atoms present in the sample, as determined by X-ray photoelectron spectroscopy (XPS) using an Al-Kα source.

[0007] The term "sulfur-functionalized graphene" refers to graphene having covalently bonded S atoms and polysulfide chains on the graphene surface. The term encompasses single-layer graphene as well as materials that include single-layer graphene in mixtures with pieces (e.g., flakes) or particles that contain multiple graphene layers. The term also encompasses graphene in which small amounts of fluorine are present as well (up to about 10 atomic %).

[0008] The dispersion prepared in step a) is a dispersion of fluorinated graphite in a solvent. The solvent is preferably an aprotic polar solvent. The solvent may preferably be selected from dimethylformamide (DMF), dimethylsulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP), glycols such as ethylene glycol, and mixtures thereof. Less polar or non-polar solvents such as acetonitrile, benzene, toluene or chlorobenzene may be used in combination with polar organic solvents (e.g., DMF, NMP, dimethylsulfoxide, dimethylacetamide).

[0009] The invention also includes embodiments in which a different solvent is used for the ultrasonic treatment and / or mechanical treatment and / or thermal treatment than the solvent used for the reaction with the metal polysulfide reagent.

[0010] The steps of ultrasonication and / or mechanical treatment and / or thermal treatment result in a mixture containing fluorinated graphene and exfoliated fluorinated graphite particles.

[0011] Sonication is typically carried out at a frequency range of 20 kHz to 100 kHz for at least 2 hours, more preferably at least 3 hours, and even more preferably at least 4 hours.

[0012] The heat treatment of the ultrasonically treated fluorinated graphite with metal polysulfides (step d) is typically carried out in an inert atmosphere at 10 to 110 o C for at least 1 hour, preferably at least 6 hours, more preferably at least 24 hours, and even more preferably at least 72 hours.

[0013] The mechanical treatment preferably comprises at least one treatment selected from high shear mixing, stirring, vigorous stirring, stirring with a magnetic bar, stirring with a mechanical stirrer. The mechanical treatment is most typically carried out by high shear mixing or stirring with a magnetic bar.

[0014] Preferred treatments in step b) are ultrasonic treatment and / or mechanical treatment. Particularly preferred is mechanical treatment (especially stirring) followed by ultrasonic treatment.

[0015] The metal in the polysulfides and sulfides in step c) is preferably an alkali metal or an alkaline earth metal, more preferably the metal is selected from sodium, potassium and magnesium, most preferably the metal is sodium.

[0016] The metal polysulfide is preferably added to the reaction mixture of step d) as a powder.

[0017] After the product of step b) containing exfoliated graphite fluoride / fluorinated graphite is contacted with the metal polysulfide reagent, the mixture is typically heated to a temperature in the range of 10-110° C., more preferably 20-100° C., even more preferably 50-90° C. Heating is preferably carried out for at least 4 hours, preferably 4 hours to 20 days, even more preferably at least 8 hours, even more preferably at least 24 hours, even more preferably at least 2 days (48 hours), or at least 3 days (72 hours). The longer the heating time, the higher the degree of sulfur functionalization.

[0018] The weight ratio (mass ratio) of the starting fluorinated graphite to the metal polysulfide is preferably in the range of 1:2 to 1:20, more preferably 1:2 to 1:10. The optimum weight ratio is about 1:8 for sodium polysulfide.

[0019] The separation step of the product (sulfur-functionalized graphene) can be carried out by known techniques such as centrifugation, sedimentation, or filtration.

[0020] The solvent used in the present method is preferably a polar solvent, which may be preferably selected from dimethylformamide (DMF), dimethylsulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMA), glycols such as ethylene glycol, and mixtures thereof.

[0021] The method of the invention makes it possible to prepare graphene containing sulfur in the form of polysulfides and sulfur (S) atoms, sodium (as counterion to the S atoms at the ends of the polysulfide chains) and fluorine atoms. Although the final sulfur-functionalized graphene usually contains residual fluorine atoms, the present method makes it possible to reliably achieve a higher sulfur mass loading than most methods known in the prior art, the sulfur loading achieved being 80% or more, since the reaction of step d) uses a mass ratio of sodium polysulfide:fluorine graphene of 8:1. o C for 48 hours, it is about 80% by weight, oC, at least 74% by weight, and at least 70% by weight at room temperature. The processes which make it possible to achieve these properties are simple and efficient, using economically efficient starting compounds.

[0022] In particular, the method of the present invention is the only wet process chemical method capable of achieving such high sulfur loadings, covalently bonded to the carbon atoms of graphene that were previously bonded to fluorine atoms, and furthermore, it is the only method that achieves high sulfur loadings at relatively low reaction temperatures.

[0023] The use of metal polysulfides instead of elemental sulfur offers the advantage of having highly nucleophilic edges that react with the electrophilic carbon atoms of the sonicated fluorinated graphite, ultimately generating covalently bonded sulfur chains on the graphene surface. This procedure results in high sulfur loading and bonding, inhibiting the "shuttle effect", while the presence of graphene provides a conductive pathway for electron transfer within the battery cell.

[0024] Thus, sulfur-functionalized graphene has desirable characteristics that enable its use as a high sulfur-containing cathode without the drawbacks of materials known in the art. In particular, its high sulfur loading combined with the covalent bonding of sulfur on the surface of graphene leads to high specific capacity and high cycling stability that are comparable to or higher than previous sulfur-containing graphene-based LSB materials from the prior art. The highest achieved specific capacity, described in Example 7, is 912 mAhg. -1 It was.

[0025] The sulfur-functionalized graphene obtained by the method of the present invention contains covalently bonded sulfur and has a sulfur loading of at least 60% by weight, preferably at least 70% by weight. The sulfur loading is determined by thermogravimetric analysis to be between 200 and 350%. o The sulfur-functionalized graphene further comprises residual fluorine and residual sodium.

[0026] In other words, the sulfur-functionalized graphene contains at least 12 atomic % covalently bonded sulfur and optionally up to 10 atomic % residual fluorine and residual sodium, where "atomic %" is determined relative to the total atoms present in the sample by X-ray photoelectron spectroscopy (XPS) using an Al-Kα source.

[0027] Preferably, the sulfur-functionalized graphene contains at least 18 atomic % sulfur, up to 8 atomic % fluorine, and up to 9 atomic % sodium, based on total atoms present in the sample, as determined by X-ray photoelectron spectroscopy (XPS) using an Al-Kα source.

[0028] The sulfur content in the sulfur-functionalized graphene according to this preparation method, determined by X-ray photoelectron spectroscopy (XPS) using an Al-Kα source, can be up to about 18.4 atomic % with respect to the total atoms present in the sample, which corresponds to a mass content of 80 wt % according to thermogravimetric analysis, as described in Example 2.

[0029] Another aspect of the present invention is the use of the above-mentioned sulfur-functionalized graphene as an LSB cathode material. The sulfur-functionalized graphene of the present invention has high specific capacity and very high retention of capacity upon cycling at both low and high C-rates.

[0030] The present invention also provides a battery comprising at least two electrodes, a separator, and an electrolyte, wherein one electrode comprises or consists of the sulfur-functionalized graphene described above.

[0031] The electrolyte may be a liquid electrolyte containing a lithium salt.

[0032] The battery can include at least two electrodes, at least one electrode made from the sulfur-functionalized graphene of the present invention applied onto a current collector (such as a carbon-coated aluminum foil), and at least one separator film disposed between the electrodes, the separator film being impregnated with an electrolyte and including a lithium foil anode.

[0033] In a particular embodiment, a two-electrode system using lithium foil as the anode was used to evaluate the performance, rate capability and cycling stability of the sulfur-functionalized graphene obtained from step (e). The sulfur-functionalized graphene was homogeneously dispersed in N-methyl-2-pyrrolidone (NMP) with the addition of polyvinyl fluoride (PVDF) and carbon black (Ketjen Black), preferably in a mass ratio of 90:5:5, and sonicated, preferably for 6 hours, to form a homogeneous paste. Further, during every 2 hours of sonication, the slurry was mixed in a planetary mixer to better distribute the components. The slurry was pasted on aluminum foil by doctor blade method (180 μm blade height). The film was then dried overnight in a vacuum oven at 80° C., after which the two electrodes were cut into 18 mm disks. The electrodes were then weighed and dried again under vacuum (40 mbar), preferably for 8 hours, in a vacuum oven at 80° C. The electrodes were transferred (under vacuum) to an Ar-filled glove box. The cathode electrode and the lithium foil were placed facing each other with a separator film between them. The separator film was soaked with the selected electrolyte. The electrodes were sealed in an airtight package and the current collectors were connected to a test device (battery tester). Prior to the actual testing of the battery cells, the open circuit voltage (E oc ) The electrodes were allowed to rest until equilibrium was reached (approximately 6 hours) and then conditioned by charging the cell at a lower voltage and lower specific current than the final voltage used. [Brief description of the drawings]

[0034] [Figure 1] FIG. 1 shows the S2p X-ray photoelectron spectrum of the product of Example 1. [Diagram 2]FIG. 2 shows the X-ray photoelectron spectra of the starting material and the product of Example 2. [Diagram 3] FIG. 3 shows the C1s X-ray photoelectron spectrum of the product of Example 2. [Figure 4] Figure 4 shows the thermogravimetric analysis of the solid product from the reaction of Example 2. The analysis was carried out in N2 atmosphere at 5°C / min up to 800°C. [Diagram 5] FIG. 5 shows the infrared spectra of (a) the starting fluorinated graphite and (b) the product of Example 2. [Figure 6] Figure 6 shows the thermogravimetric analysis of the solid product from the reaction of Example 3. The analysis was carried out in a N2 atmosphere at 5°C / min up to 800°C. [Figure 7] Figure 7 shows the thermogravimetric analysis of the solid product from the reaction of Example 4. The analysis was carried out in a N2 atmosphere at 5°C / min up to 800°C. [Figure 8] Figure 8 shows the thermogravimetric analysis of the solid product from the reaction of Example 5. The analysis was carried out in a N2 atmosphere at 5°C / min up to 800°C. [Figure 9] 9 shows the thermogravimetric analysis of the solid product from the reaction of Example 6. The analysis was carried out in a N2 atmosphere at 5° C. / min up to 800° C. [Figure 10] FIG. 10 shows a scanning electron microscope (SEM) image of a film of the electrode material (prepared as described in Example 7 and applied onto aluminum foil). [Figure 11] FIG. 11 is an electrochemical characterization of the product from Example 2, showing a) cyclic voltammetry curves in 1 M LiTFSI in 1:1 DOL:TTE at various scan rates; b) galvanostatic charge-discharge profile at 0.1 C (0.17 Ag−1). [Figure 12] FIG. 12 shows rate performance testing of the product from Example 2 in 1M LiTFSI in 1:1 DOL:TTE at various C-rates (specific currents). [Figure 13]FIG. 13 shows the specific capacity and coulombic efficiency of the products from Example 2 in 1 M LiTFSI in 1:1 DOL:TTE: (a) 0.1C (0.17A g-1), (b) 0.2C (0.33A g-1), and (c) 1C (1.7A g-1). [Figure 14] FIG. 14 shows a scanning electron microscope (SEM) image of the battery test material film from Example 2 after being tested for 250 charge-discharge cycles. [Figure 15] 15 shows the specific capacity and coulombic efficiency of the product from Example 6 in 1M LiTFSI in 1:1 DOL:TTE.

[0035] Materials and Methods Graphite fluoride (>61 wt% F), Na2S·9H2O, sulfur and 1-methyl-2-pyrrolidinone anhydrous, 99.5% were purchased from Sigma-Aldrich. Acetone (pure) and ethanol (anhydrous) were purchased from Penta (Czech Republic). All chemicals were used without further purification.

[0036] FT-IR spectra were measured on an iS5 FTIR spectrometer (Thermo Nicolet) using the KBr pellet accessory. Spectra were recorded by summing 50 scans using pure KBr for background acquisition.

[0037] X-ray photoelectron spectroscopy (XPS) was performed on a PHI VersaProbe II (Physical Electronics) spectrometer using an Al-Kα source (15 kV, 50 W). The data were deconvoluted using the MultiPak (Ulvac, Inc.) software package.

[0038] Samples were also analyzed by scanning electron microscopy using a Hitachi SU6600 instrument with an accelerating voltage of 5 kV. For these analyses, a dispersion of material in ethanol (concentration, approximately 0.1 mg / ml) was deposited on a carbon-coated copper grid. -1) was deposited and allowed to dry.

[0039] Thermal analysis was carried out using a STA449 C Jupiter Netzsch instrument.

[0040] Cyclic voltammetry (CV) and galvanostatic charge-discharge with potential limitation (GCPL) were performed on a Bio-Logic battery tester (BCS-810) controlled by BT-Lab software (version 1.64).

[0041] The following sections define battery metrics used herein and generally accepted in the art: Specific Capacity (C) of the Electrode Material (in mAhg -1 ) is calculated from the galvanostatic charge / discharge curves according to the following formula:

number

[0042] The coulombic efficiency (CE%) for each cycle is calculated according to the following formula:

number

[0043] <Example 1: Synthesis of sodium polysulfide (3-hour reaction)> 1 In a glass spherical flask, 4.8 g of sodium sulfide nonahydrate (Na2S·9H2O) was dissolved in 20 ml of a water-ethanol mixed solvent (volume ratio 1:1), followed by the addition of 0.64 g of sulfur (S). oThe solution was stirred with a Teflon-coated magnetic bar at 40° C. for 3 h, at which point the solution turned from yellow to dark orange, indicating that the chain length of the polysulfides was gradually increased. The solvent was removed by rotary evaporation (30 o C), and the residue was ground in a mortar to produce a fine powder.

[0044] X-ray photoelectron spectroscopy on the product of Example 1 (Figure 1) showed that the reaction of Na2S with S leads to sodium polysulfides by displaying four doublets, each representing a different chemical state of sulfur. The first 162 eV is the S2p of the terminal sulfur. 3 / 2 whereas the doublet at 163.5 eV is assigned to the central sulfur.

[0045] Example 2: Synthesis of sulfur-functionalized graphene (80 o C, 1:8 mass ratio)>2 To prepare sulfur-functionalized graphene (GPS), first, 250 mg of graphite fluoride was dispersed in 15 ml of NMP using a 50 ml glass spherical flask. The flask was covered and stirred for 3 days. It was then sonicated for 4 hours to achieve better exfoliation. After exfoliation, 2 g of the product from Example 1 was added, and the mixture was heated in an oil bath at 80 °C in a N2 atmosphere while magnetically stirring using a Teflon-coated magnetic bar. o The reaction was refluxed at -80 °C for 48 h. After the reaction was complete, the mixture was left to cool and transferred to a 50 ml Falcon centrifuge tube. The solid particles (product) were separated from the solvent and by-products were separated by centrifugation at 15000 rcf for approximately 10 min. The supernatant was discarded and the tube was refilled with the next washing solvent. The sample was homogenized by shaking and sonication for at least 1 min to redisperse the precipitate in the new solvent. Washing was performed with different solvents: NMP (3x), acetone (3x), ethanol (3x), and distilled water (3x), then refilled with distilled water. Finally, the aqueous mixture was diluted with water at -80 °C for 1 h. o C, and after 3 hours, it was placed in a freeze dryer (-108 o C, 0.4 mbar) for 2 days. The final product was a fine powder.

[0046] X-ray photoelectron spectroscopy on the starting fluorographite (FG) and the product of Example 2 (Figure 2) shows that the F1s peak is much lower than that of FG, indicating the insertion of sulfur from the polysulfides and some residual sodium, possibly at one polysulfide edge, and that the S2p and Na1s peaks appear, confirming the reaction between PS and FG, indicating successful defluorination of GPS. Furthermore, the deconvoluted C1S spectrum of the GPS material shows that the sp 2 A major peak at 284.8 eV corresponding to the bond was shown, and another peak at 285.6 eV corresponding to carbon covalently bonded to S appeared (Figure 3). The atomic ratios of each component are shown in Table 1.

[0047] The actual sulfur content was measured by thermogravimetric analysis (TGA), where the weight loss in the temperature range of 200–350 °C is due to the release and evaporation of sulfur (Figure 4). The thermogram from GPS shows that the weight loss in the temperature range of 200–350 °C is due to the release and evaporation of sulfur (Figure 4). o C, and a residual mass of about 20 wt. % (about 80 wt. % sulfur loading).

[0048] FT-IR analysis was performed to better understand the chemical structure of the material. The defluorination of the starting material FG and the isolation of the product (GPS) after the reaction and the presence of the CS covalent bond were verified. The CF band (~1200 cm -1 ) decreases to about 1570 cm -1 A new band appeared at about 1060 cm, which indicates the successful defluorination and the formation of C=C bonds (aromatic ring stretching), respectively (Figure 5). In addition, a new band appeared at about 1060 cm, which is due to the covalent C-S bond (CS stretching). -1 Another peak at

[0049] [Table 1] <Example 3: Synthesis of sulfur-functionalized graphene (50°C)> The same procedure as in Example 2 was carried out, but instead of heating at 80° C. for 48 hours, heating was carried out at 50° C. for 48 hours.

[0050] Thermogravimetric analysis (TGA) was performed to verify the sulfur loading in this example (Figure 6). The GPS thermogram shows that the sulfur loading is o C), and a residual mass of about 25 wt. % (about 75 wt. % sulfur loading, which may be about 16 atomic % based on XPS. Note that XPS is a surface analysis technique).

[0051] Example 4: Synthesis of sulfur-functionalized graphene (room temperature) The same procedure as in Example 2 was followed, but instead of heating the mixture at 80° C. for 48 hours, it was left at room temperature for 48 hours.

[0052] Thermogravimetric analysis (TGA) was performed to verify the sulfur loading in this example (Figure 7). o C thermogram is 200~350 o C, and a residual mass of about 29 wt. % (about 71 wt. % sulfur loading).

[0053] <Example 5: Synthesis of sulfur-functionalized graphene using preheated graphite fluoride (Comparative Example)> The same procedure as in Example 2 was followed, but FG was heat treated for 48 hours in the absence of the product (polysulfide) from Example 1. First, 250 mg of graphite fluoride was dispersed in 15 ml of NMP using a 50 ml glass bulb flask. The flask was covered and stirred for 3 days. It was then sonicated for 4 hours to achieve better exfoliation. Then, 120 mg of graphite fluoride was dispersed in NMP without the addition of sodium polysulfide. o The mixture was heated at 80°C for 48 hours. The product of this reaction was significantly defluorinated and contained only 15 atomic % fluorine. After these 48 hours of heating, sodium polysulfide was added and the mixture was heated at 80°C for 48 hours. Thermogravimetric analysis (TGA) was performed to verify the sulfur loading in this example (Figure 8). The thermogram of GPS with preheated graphite fluoride shows a temperature gradient between 200 and 350°C. oC, and a residual mass of about 67 wt. % (about 33 wt. % sulfur loading). The low sulfur content in this case is comparable to that of the 120 o This is due to the defluorination of fluorinated graphite during the first heat treatment with C; i.e., if carbons are not bonded to fluorine atoms, they are not electrophilic and cannot react with polysulfide chains. This example clearly demonstrated the important role of fluorine in fluorinated graphite for the covalent bonding of graphene carbon with polysulfides during the reaction (step (d) of the present invention).

[0054] Example 6: Synthesis of sulfur-functionalized graphene (80°C, mass ratio 1:4) The same procedure was followed as in Example 2, but instead of using 2 g of PS, 1 g was used to reduce the FG / PS mass ratio in the reaction from 1:8 (Example 2) to 1:4.

[0055] Thermogravimetric analysis (TGA) was performed to verify the sulfur loading in this example (Figure 9). o C1:4 mass ratio thermogram is 200~350 o C, and a residual mass of about 26 wt. % (about 74 wt. % sulfur loading).

[0056] Example 7: Product from Example 2 (80 o Electrochemical test in Li-S full cell using C, mass ratio 1:8)

[0057] The active material (sulfur-functionalized graphene, GPS from Example 2) was uniformly dispersed in N-methyl-2-pyrrolidone (pa≧99%, Sigma-Aldrich) with binder polyvinylidene fluoride (PVDF, Sigma-Aldrich) and conductive carbon Ketjen black (AkzoNobel) in a ratio of 90:5:5 and sonicated for 6 hours to form a uniform paste. Further, during every 2 hours of sonication, the slurry was mixed in a planetary mixer (Thinky ARV-310LED) to better disperse the components. The slurry was pasted onto carbon-coated aluminum foil (Cambridge Energy Solutions, 15 μm thick) using a doctor blade technique (Erichsen, Quadruple Film Applicator, model 360). The film was then dried overnight in a vacuum oven at 80° C., after which electrodes of 18 mm diameter were cut. Prior to testing, the resulting membrane was examined by scanning electron microscopy, which showed that sulfur particles coated and adhered onto the graphene sheets with a uniform distribution (Fig. 10a, b). For the assembly of the battery device, the GPS electrode was placed in a sleeve (El-Cell insulator sleeve with a 0.26 mm thick Whatman® glass microfiber paper separator). The separator membrane was soaked with about 100 μl of electrolyte. 1 M LiTFSI (lithium bis-trifluoromethanesulfonimide, MTI) in a 1:1 mixture of DOL (Dioxolane, Aldrich) and TTE (1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, TCI) was used as the electrolyte. All solvents were dried overnight over molecular sieves before use. A lithium foil disk with a diameter of 18 mm was used as the anode, and both electrodes were enclosed inside the sleeve with a stainless steel plunger, while the entire device was clamped and connected to a battery tester for analysis.

[0058] Prior to testing the devices, the electrode materials were conditioned as follows: The electrodes are allowed to rest until they reach voltage equilibrium (usually about 6 hours), then the potential is held at 1.5 V for 3 hours.

[0059] The above cells were tested by cyclic voltammetry (CV) and charge / discharge profiling. First, CV profiling was performed at 0.1, 0.2, and 0.5 mVs. -1 In all cases, the anodic peak during charging is due to the oxidation of the cathode, which is completed in two steps, and the broad peak at about 2.45 V is due to the oxidation of Li2S 1-2 Li2S n (n>2) and the formation of elemental sulfur. The reduction is also completed in two clearly separated steps: the peak at 2.25 V corresponds to the conversion of LiS n (4≦n≦8), while the peak at 1.8 V is due to the subsequent reduction of elemental sulfur to LiS n Li2S 1-2 (Figure 11a). Figure 11b shows the electrochemical profile of the galvanostatic charge / discharge of the sulfur-functionalized graphene cathode. The shape of the curve is -1 The capacity was well maintained for more than 75 cycles at a specific current of 1C (1.67Ag -1 ) at 496mAhg -1 , and 2C(3.3Ag -1 ) even at 298mAhg -1 The capacity of 0.2C (0.33Ag) shows good rate characteristics. -1 ) the cathode is about 800mAhg -1 The initial capacity of the material is recovered at 636mAhg at 1C (Figure 12). Stability testing of the material shows excellent results at both high and low specific currents. The initial capacity is 636mAhg at 1C (Figure 13). -1 to 912mAhg at 0.1C -1 (0.17Ag -1 ) and the cell has a capacity of 720mAhg after 200 cycles at 0.2C. -1 (0.33Ag -1 ), and 706mAg after 100 cycles at 0.1C -1Even at low rates, the charge-discharge stability was very high (Figure 13). This value was 635 mAhg for the active material (90%). -1 This is equivalent to 0.1C(0.17Ag -1 508mAhg for total electrode mass (GPS, 80% sulfur) after 100 cycles at -1 The coulombic efficiency remains at 96.8% for 100 cycles, corresponding to very low material loss during cycling. After the tests, the test material was peeled from the film, washed and examined under a scanning electron microscope, showing perfect preservation of the structure due to the strong interactions between graphene and sulfur, even after 250 charge-discharge cycles (Figure 14).

[0060] Example 8: The product from Example 6 (80 o Electrochemical test in Li-S full cell using C, mass ratio 1:4)

[0061] The same procedure as in Example 6 was followed, but instead of using the product of Example 2, the product of Example 6 was used. Li foil was used as the anode, and LiTFSI (lithium bis-trifluoromethanesulfonimide, MTI) 1M in a 1:1 mixture of DOL (dioxolane, Aldrich) and TTE (1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, TCI) was used as the electrolyte. Before testing the device, the electrode material was conditioned as follows: the electrode was left to reach voltage equilibrium (usually about 6 hours) and the potential was held at 1.5 V for 3 hours.

[0062] The stability test of this material shows good results at low current densities. The initial capacity is 0.2 C (0.33 Ag -1 ) at 686mAg -1 and the cell had 784mAhg after 100 cycles. -1 Even at this rate, the charge remained very stable (Figure 15). This value was 705 mAhg for the active material (90%). -1 This is equivalent to 0.2C(0.33Ag -1) corresponds to 522 mAhg for the total electrode mass (GPS, 74% sulfur) after 100 cycles. The coulombic efficiency remains at 96% for 100 cycles, corresponding to very low material loss during cycling. These figures are very close to those of Example 7, with 685 mAhg for the active material (90% active). -1 761mAhg after 100 cycles corresponding to -1 (Figure 13b) and 0.2C (0.33Ag -1 ) after 100 cycles, 547mAhg for total electrode mass (GPS1:8, 80% sulfur) -1 Similarity in results was expected since all parameters were kept the same except for the FG:PS mass ratio. Overall, the GPS1:8 material performs slightly better due to its higher sulfur mass loading.

Claims

1. a) providing a dispersion of fluorinated graphite containing at least 40 atomic % fluorine; b) subjecting the dispersion of fluorinated graphite to ultrasonic treatment for exfoliation; c) preparing a metal polysulfide starting from a metal sulfide and sulfur; d) contacting the product from step b) with the product from step c) at a temperature in the range of 10 to 110° C.; e) separating the solid product formed in step d) from the solution.

2. A method for preparing sulfur-functionalized graphene as described in claim 1, wherein in step b), the dispersion of fluorinated graphite is subjected to a mechanical treatment and / or a thermal treatment in addition to an ultrasonic treatment.

3. 3. The method according to claim 1 or 2, wherein the dispersion prepared in step a) is a dispersion of fluorinated graphite in an aprotic polar solvent, optionally in combination with a non-polar solvent.

4. 4. The method according to claim 2 or 3, wherein in step b) the dispersion is subjected to a mechanical treatment followed by ultrasonic treatment, said mechanical treatment being selected from high shear mixing, stirring, vigorous stirring, stirring with a magnetic bar, stirring with a mechanical stirrer.

5. 5. The process according to any one of claims 1 to 4, wherein the metal in the polysulfides and sulfides in step c) is an alkali metal or an alkaline earth metal, more preferably the metal is selected from sodium, potassium and magnesium.

6. 6. The process according to any one of claims 1 to 5, wherein after contacting the product of step b) with the metal polysulfide reagent, the mixture is heated to a temperature in the range of 10 to 110°C for at least 4 hours, preferably for at least 2 days.

7. 7. The method according to any one of claims 1 to 6, wherein the weight ratio of the starting materials, said fluorinated graphite and said metal polysulfide, is in the range of 1:2 to 1:20, more preferably 1:2 to 1:

10.

8. The graphene has covalently bonded sulfur and has a sulfur loading of at least 60% by weight, the sulfur loading being between 200 and 350%. o C., wherein the covalently bonded sulfur is in the form of covalently bonded sulfur atoms and polysulfide chains on the surface of the graphene.

9. 9. The sulfur-functionalized graphene of claim 8 having a sulfur loading of at least 70 wt.%.

10. 10. Sulfur-functionalized graphene according to claim 8 or 9, containing up to 10 atomic % fluorine, the atomic % being determined relative to the total atoms present in the sample, determined by X-ray photoelectron spectroscopy using an Al-Kα source.

11. Use of the sulfur-functionalized graphene according to any one of claims 8 to 10 as a cathode material in a lithium-sulfur battery.

12. A battery comprising at least two electrodes, a separator and an electrolyte, wherein one electrode comprises or consists of the sulfur-functionalized graphene of any one of claims 8 to 10.

Citation Information

Patent Citations

  • Sulfur-hydroxylated graphene nanocomposites for rechargeable lithium-sulfur batteries and methods of making the same

    US20140255795A1